Pengaruh Pemberian Ekstrak Pacar Kuku (Lawsonia inermis L) Untuk Penyembuhan Luka Bakar Pada Mencit Putih - Elfia, Linda; Abeiasa, M Saka; Humaira, Vilma; Rahmi, Fatihatur (Jurnal Medisains Kesehatan, 2022)
Burns are injuries caused by direct contact or exposure of the body to sources of heat, chemicals, electricity and radiation. Burns not only cause damage to the skin but can also affect the body's system. Therefore, burns require special attention in handling. Lawsonia inermis L. is a plant that contains compounds that play a role in wound healing such as flavonoids, saponins and tannins. This study aims to determine whether there is an effect of henna leaf extract on healing burns. Nail henna leaf extract was made by maceration using 96% ethanol as solvent. This study used male mice as test animals which were divided into 5 groups, the positive control group was not given treatment, the negative control group was given vaseline flavum and 3 groups were given henna leaf extract with concentrations of 20%, 40% and 60%. Burns were made by using preheated solder for 5 minutes. The intervention was carried out once a day. The results of the statistical analysis of the One Way ANOVA test showed that the concentration of fast burn healing was 40%.